The tribological properties of lanthanum borate nanoparticles with different morphologies as lubricant additive in rapeseed oil. (October 2019) - Lin, Wang; Gu, Kecheng; Chen, Boshui; Wang, Xin
Abstract: Sheet-like, Petal-like and Ball-like lanthanum borate nanoparticles were prepared by hydrothermal method (abbreviated as SLBN, PLBN and BLBN, respectively). The morphologies in rapeseed oil (abbreviated as RO) were characterized by scanning electron microscope (SEM). The antiwear and friction-reducing performances of lanthanum borate nanoparticles in rapeseed oil were evaluated on a four-ball tribo-tester. Moreover, the worn steel ball surface was investigated by SEM, X-ray photoelectron spectroscopy (XPS) and Surface Profiler. The result shows that PLBN and SLBN have a thickness of 10nm and 30nm, which exhibits excellent dispersing ability in rapeseed oil, and BLBN have a diameter of 50-120nm. Furthermore, PLBN show a better friction-reducing and antiwear performance. Meanwhile, 2D appearance indicated the worn steel ball lubricated with RO+SLBN have the more shallow and narrow scratches, which consistent with 3D topography. The excellent friction-reducing and antiwear performances attribute to tribochemical film, which contains B2 O3 and La2 O3 .